Epidemiology, management, and outcome of infection, sepsis, and septic shock in a German emergency department (EpiSEP study) - Wolfertz, Nicole; Böhm, Lennert; Keitel, Verena; Hannappel, Oliver; Kümpers, Philipp; Bernhard, Michael; Michael, Mark (Frontiers in Medicine, 2022)
Background: The adjacent conditions infection, sepsis, and septic shock are among the most common causes of treatment in the emergency department (ED). Most available data come from intensive care units (ICU) and include nosocomial infections acquired during hospitalization. Epidemiological data from German EDs are not yet available, although the ED is one of the first points of contact for patients. The aim of this study was to investigate the epidemiology, causes, diagnosis, mortality and treatment of patients with infections in the ED. Methods: In this retrospective, single-center observational study, routinely collected data from the patient data management system and from the hospital information system were analyzed. All adult patients who presented to the ED in connection with an infection during the study period from 01/01 to 02/28/2019 were included. Exclusion criteria were age ≤17 years and incomplete records. Three groups (I. Infection, II. Sepsis, and III. Septic shock) were defined according to SEPSIS-3 definitions. Results: During the study period, a total of 6,607 patients were treated in the ED. Of these patients, 19.3% (n=1,278) had an infection (mean age 56±23 years, 50% female). The sites of infection were distributed as follows: Respiratory tract 35%, genitourinary tract 18%, maxillofacial/ears/nose/throat 14%, abdomen 13%, soft tissues 10%, central nervous system 1%, other cause 3%, or unknown cause 6%. Infection only, sepsis and septic shock were present in 86, 10 and 3%, respectively. There were differences in various emergency medicine sepsis scores across the predefined groups [I vs. II vs. III: SOFA (pts.): 1±1 vs. 4±2 vs. 7±3 (p<0.0001)]. In the three groups, blood cultures were obtained in 34, 81, and 86%, of cases, respectively and antibiotics were administered in the ED in 50, 89, and 86%, of cases respectively. The 30-day mortality in the three groups was 1.6, 12.0, and 38.1%, respectively. Conclusion: This study is the first to show the incidence, management, and outcome of patients classified as infection, sepsis, and septic shock in a German ED. The findings of our real-world data are important for quality management and enable the optimization of treatment pathways for patients with infectious diseases.